2021
DOI: 10.1029/2020rg000725
|View full text |Cite
|
Sign up to set email alerts
|

Nordic Seas Heat Loss, Atlantic Inflow, and Arctic Sea Ice Cover Over the Last Century

Abstract: Poleward ocean heat transport is a key process in the earth system. We detail and review the northward Atlantic Water (AW) flow, Arctic Ocean heat transport, and heat loss to the atmosphere since 1900 in relation to sea ice cover. Our synthesis is largely based on a sea ice‐ocean model forced by a reanalysis atmosphere (1900–2018) corroborated by a comprehensive hydrographic database (1950–), AW inflow observations (1996–), and other long‐term time series of sea ice extent (1900–), glacier retreat (1984–), and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 210 publications
(429 reference statements)
1
37
0
1
Order By: Relevance
“…The increased ocean heat transport as represented by the shift in EOF1 in 2000 and the de-seasoned EOF model (Figure S2 in Supporting Information S1), the "switching" role of the SPG and increased AW inflow with the NIIC, collectively suggest an increase in the oceanic heat transport to the Nordic Seas over the 1979-2020 period. These findings are aligned with a suite of recent studies on the heat budget of the Nordic Seas recently reviewed by Smedsrud et al (2022) and provide a separation of the response in SST into independent underlying factors. Increases in AW inflow in part contradict evidence for decreases in Atlantic meridional overturning circulation (AMOC) (e.g., Smeed et al, 2018), which are based on deepwater moorings further south.…”
Section: Regional Connectivitysupporting
confidence: 85%
See 1 more Smart Citation
“…The increased ocean heat transport as represented by the shift in EOF1 in 2000 and the de-seasoned EOF model (Figure S2 in Supporting Information S1), the "switching" role of the SPG and increased AW inflow with the NIIC, collectively suggest an increase in the oceanic heat transport to the Nordic Seas over the 1979-2020 period. These findings are aligned with a suite of recent studies on the heat budget of the Nordic Seas recently reviewed by Smedsrud et al (2022) and provide a separation of the response in SST into independent underlying factors. Increases in AW inflow in part contradict evidence for decreases in Atlantic meridional overturning circulation (AMOC) (e.g., Smeed et al, 2018), which are based on deepwater moorings further south.…”
Section: Regional Connectivitysupporting
confidence: 85%
“…Strong seasonal variability is also evident in the annual build-up and melt of sea-ice. Summertime sea-ice melt along the east Greenland shelf absorbs considerable amounts of latent heat, and releases cold, fresh waters initially lowering summer SST in the western part of the Nordic Seas (Smedsrud et al, 2022). This is reflected in the high frequency signal captured in EOF3 (Figure 6).…”
Section: Seasonal Control Of Sstmentioning
confidence: 99%
“…We note that this paper does not cover all aspects of the Arctic Ocean dynamics. Recently some other Arctic Ocean topics have also been reviewed, including ocean circulation dynamics in general (Timmermans and Marshall, 2020), freshwater in the 2010s (Solomon et al, 2021), ocean heat transports in relation to Arctic sea ice (Docquier and Koenigk, 2021;Smedsrud et al, 2022), and Arctic Atlantification and Borealization (Polyakov et al, 2020a;Ingvaldsen et al, 2021).…”
Section: Paper Outlinementioning
confidence: 99%
“…5.6d). The cooling trend (~−0.06°C yr −1 ) in mean August SSTs in the north-central Barents Sea region remains a notable exception (Timmermans et al 2020), although the cooling trend is not observed for most other months, nor for other parts of the Barents Sea (Lind et al 2018;Smedsrud et al 2022). Further, in this region Barents Sea waters contact cooler, fresher Arctic waters, and shifts in this boundary complicate interpretation of trends (see Barton et al 2018).…”
Section: S270mentioning
confidence: 99%